Analisis Manajemen Risiko Keselamatan Dan Kesehatan Kerja Dengan Metode Hazard Identification Risk Assessment and Risk Control (HIRARC) Di Reformed Millenium Center of Indonesia - P., Subandri A.; Prabowo, Herry Agung (Proceeding Mercu Buana Conference on Industrial Engineering, 2020)
Safety and health of work is a matter that capture many organizations today because they inlude humanitaries-conscious, economic cosr and benefits, legal aspects, accountability and the organization’s own image. The study will be concucted on risk identification safety and health of work, risk assessment safety and health of work as well as on how safety and health of work action on risk control involves the method of Hazard Identification Risk Assessment and Risk Control (HIRARC) on activities preventive maintenance air conditioning (AC) at Reformed Millenium Center of Indonesia (RMCI) Kemayoran. Assessment method use AS/NZS 4360 : 2004, risk assessment matrix. According to file proccessing obtained a high risk value. To risk group at high risk levels as 4 variables could edanger workers and jobs. Whereas for classification at medium risk level it was found to be as 6 variables.